The Titan Atlas: Prototypes for the Configuration of its Iconography in the Figurative Arts of Classical Antiquity - Valtierra Lacalle, Ana (Eikón / Imago, 2020)
The figure of the Titan Atlas is one of the most prolific in the history of art, and one of the most stereotypical in iconography. The most common representation is the titan holding the celestial vault on his shoulders. In the case of ancient Greek is generally represented with the passage in which Heracles replaces him while he goes looking for the apples of the Hesperides. It is a very prolific image in art. Although, studies that attempt to mark the turning point in this type of iconography of a mature and bearded man, kneeling on the ground and holding the celestial vault on his shoulders are scarce.